KONTRIBUSI IMAM AL-NAWAWI DALAM PENGEMBANGAN MADHHAB SHAFIâI - Aminuddin, Luthfi Hadi (Justicia Islamica, 2011)
In the history of Shafiiâs madhhab, the figure of Imam al-Nawa wi has a very significant role. The results of his Â ijtihadÂ  is always used as a Shafi`iyah scholar reference, even when the scholars differed in opinions, then his idea regarded as "the end" of that difference dispute. This paper, intended to explore why the figure of al-Nawa wi have such a privileged position in the madhhab Sha fii. Through the historical approach, the author have found the answer to that. First, al-Nawa wi is seen as a unifier Â Shafiiâs madhhab. In his hands, two school of Shafiâi madhhab, Khurasan and Iraq can be reconciled. Second, Al-Nawa wi have managed to put the principles tarjih, to select the strongest opinion from a variety of opinion among al-Sha fiiâs madhhab. Therefore, al-Nawawi is known as the al-mujtahid al-murajjih or mujtahid al-tarjih, the mujtahid who are not just memorize the ijtihad of Imam al-Shafiâi, but know the sources of Imam al-Shafiâiâs opinion, able to describe and explain his opinion, make an analogy (qiyas) related to his opinion in problem solving, even select a strong opinion among opinions that exist.